Depression in Patients with Systemic Lupus Erythematosus - Afriando, Redho (Scientia Psychiatrica, 2023)
Depression is one of the highest incidences of depression with a considerable burden of depression. Depression is found in patients with SLE. To date, there is no clear understanding of the research relationship between depression and sleep quality in patients with systemic lupus erythematosus (SLE). Thus, patients with depression who have a poor quality of life, especially in the components of self-care and discomfort conditions. There is a moderate correlation with sleep quality in SLE patients. This paper will examine the relationship between depression and patients with SLE2.